Reflections of a Member of the Bicentennial Class on the Bicentennial Symposium - Gold, Jessica (YJBM, 2011)
This perspective piece explores what it means to be a first-year medical student at Yale School of Medicine during its bicentennial year. At first, it seemed like a hefty burden to bear. However, upon listening to Dr. Eric Kandel speak at the Bicentennial Symposium at Yale on April 28, 2011, it became clear what it means to be a part of the future of science and medicine at Yale.